HOW FAR HAS " TIME -SPENT– ON-THE-TASK" BY PUPILS AND TEACHERS PROVED TO BE CRUCIAL VARIABLE IN CLASSROOM RESEARCH? - EL KOLLI, Larbi (Journal of Human Sciences, 2008)
The question wich arises nowadays; is whether the variable " time spent on the task " can be really considered as crucial in the teacher ’ s and pupil’s lives in the classroom. The study also shows that this variable can be used by teacher as an effcient tool to control pupil’s performance on a particular task.But the most important issue in this study is that teachers should find a powerful strategy that enable them to place greater control over time that can be spent by pupils in and outside the school, otherwise pupils cannot learn in a more afficient way.